Os significados socialmente construídos na relação vítima-agressor à luz do interacionismo simbólico - Heliane Anghinetti (2019)
The study is linked to the National Project for Women, Para Elas, Por Elas, Por Eles e Por Nós, carried out by the Federal University of Minas Gerais, with support from the Ministry of Health. There were 13 interviews with women victims of aggression who sought the Reference Center on/of Assistance to Women in Situation of Violence “Centro de Referência de Atendimento à Mulher em Situação de Violência” in six Brazilian municipalities, elected by the National Forum to Combat Violence against Women as citizenship territories and designated as municipalities of Campo and Forest. Objective: discuss the meaning constructed by the women of those six Brazilian municipalities, victims of violence under the Symbolic Interactionism. Methodology: it is a qualitative study whose main theme is the confrontation of violence against women. The database was obtained through in-depth interviews, recorded and later transcribed. The data will be analyzed under the methodological theory of Symbolic Interactionism. Conclusions: the life in group is a process of construction of joint actions, where the members interpret and act when facing situations presented. It was possible to perceive, through research, that violence against women is understood as physical aggression, linked to humiliation, offense and deprivation (of material, food, freedom etc.); this meaning of violence permeates their understanding of the aggressions suffered by their respective companions. Most interviewees claimed to recognize the exercise of male power over them (power that cause physical or psychological harm). Throughout the development of the social interaction, those women have changed the meaning of violence for them: aggression of any kind (sexual and psychological, and physical) became no longer accepted and started to be fought, in the same way, their respective companion ceased to be seen as protector/companion/provider of affection and material support becoming a person who offers real risk (a real agressor).